Influence of flow rate of linear alkylbenzene in film sulfonation reactor on concentration of target product and tetralines and sulfones concentration; Catalytic Hydroprocessing In Oil Refining (STS-HydroCat - 2021) - Dolganov I. M. Igor Mikhailovich; Dolganova I. O. Irena Olegovna; Solopova A. A. Anastasia Alexandrovna; Pasyukova M. A. Mariya Alekseevna; Bunaev A. A. Ayur Alekseevich; Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna (2021, 2021)
Title screen